Case report: Central alveolar hypoventilation in a survivor of cardiopulmonary arrest - Wang, Fajun; Darby, Joseph (Frontiers in Neurology, 2023)
Introduction Ondine’s curse is a rare respiratory disorder that is characterized by central alveolar hypoventilation (CAH) during sleep. It is most commonly congenital. However, it can also be acquired very rarely. Herein, we report a young survivor who developed CAH following cardiopulmonary arrest. Case presentation A 35-year-old man was admitted to the Intensive Care Unit following unwitnessed cardiopulmonary arrest. Following resuscitative interventions, he remained comatose. Early diagnostic testing showed elevated neuronal specific enolase (28.7 ng/ml), absent cortical responses on evoked potential testing and MRI evidence of restricted diffusion in the cerebellum, hippocampi, juxtacortical white matter, superior cerebellar peduncles, dorsal pons, dorsolateral medulla, and upper cervical spinal cord. Ten days following admission, the patient remained comatose and underwent tracheostomy. He subsequently began to emerge from coma but had persistent unexplained hypotension and bradypnea necessitating ongoing vasopressor and respiratory support. Repeat MRI on hospital day 40 revealed residual FLAIR hyperintensities in the medulla within the nucleus tractus solitarius (NTS). After being discharged to long-term acute care facility, he was successfully liberated from mechanical ventilation 70 days post arrest. Conclusion We report the first survivor of cardiopulmonary arrest who was complicated by CAH and hypotension with MRI verified ischemic injury to the bilateral NTS regions. Despite this injury, ventilator and vasopressor dependency resolved over a period of 10 weeks. Our case highlighted the essential functions of NTS in regulating the respiratory and cardiovascular systems.